2004
DOI: 10.1162/089892904322755548
|View full text |Cite
|
Sign up to set email alerts
|

Serial Position Effects in Auditory Event-related Potentials during Working Memory Retrieval

Abstract: Abstract& It is established that recall of an item from a list of sequentially presented items is sensitive to the item's position in the memorized list. However, little is known about the brain mechanisms that mediate these serial position effects. Studies of working memory retrieval using event-related potentials report amplitude reductions during retrieval (auditory cortical N100, neocortical late positive wave [LPW]) as memory load increases. We tested the hypothesis that N100 and LPW amplitudes to probes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…Although the P3 component may not be a direct index of storage processes, memory for items that elicit a P3 is better than items that do not elicit a P3, even under task conditions that require immediate or delayed retrieval (Golob & Starr, 2004;Paller, McCarthy, & Wood, 1988). The close relationship of P3 amplitude and delayed retrieval also supports the view that the component is one of the series of processes that reflect the encoding of events for storage in memory.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the P3 component may not be a direct index of storage processes, memory for items that elicit a P3 is better than items that do not elicit a P3, even under task conditions that require immediate or delayed retrieval (Golob & Starr, 2004;Paller, McCarthy, & Wood, 1988). The close relationship of P3 amplitude and delayed retrieval also supports the view that the component is one of the series of processes that reflect the encoding of events for storage in memory.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, P300 amplitude increases linearly from probe stimuli of the initial to ending list items, suggesting that recognition primacy and recency effects reflect different processing mechanisms (Golob & Starr, 2004). To date, the majority of studies have assessed serial position in the auditory modality, with no evidence currently available that similar recognition serial position ERP effects occur for visual probes.…”
Section: Serial Position Memory and Event-related Potential Effectsmentioning
confidence: 99%
“…Multiple top-down cognitive factors have been shown to influence the N100 such as attention (Bennett, Golob, & Starr, 2004; Hillyard, Hink, Schwent, & Picton, 1973), short-term memory (Conley, Michalewski, & Starr, 1999; Golob & Starr, 2004), and motor efference copy when speaking (Heinks-Maldonado, Mathalon, Gray, & Ford, 2005; Houde et al, 2002). Also previous studies found hemispheric differences around 100 ms within the auditory cortex of adults who stutter (Beal et al, 2010; Liotti et al, 2010; Salmelin R, Schnitzler A, Schmitz F, Jancke L, Witte OW et al, 1998), whereas the 100 ms group differences found in the current study appear to be bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…In this substantial literature (see Kotchoubey, 2002or Verleger, 1997 for a review), the most consistent finding is the elicitation of a sustained, parietal positivity to the probe (irrespective of probe type) with a monotonous increase in latency as memory set size increases (e.g., Blumhardt, 1996;Pelosi et al, 1992Pelosi et al, , 1995Pelosi et al, , 1998Starr and Barrett, 1987). Moreover, the manifestation of a P300 during the encoding phase has also been found to be a predictor of successful retrieval in the test phase (Chao and Knight, 1996;Golob and Starr, 2004;Kotchoubey et al, 1996;Patterson et al, 1991).…”
Section: Introductionmentioning
confidence: 96%